2021
DOI: 10.3390/plants10112264
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Different Priming Agents for Improving Germination and Early Seedling Growth of Local Tunisian Barley under Salinity Stress

Abstract: The current work aimed to investigate the effect of seed priming with different agents (CaCl2, KCl, and KNO3) on germination and seedling establishment in seeds of the barley species of both Hordeum vulgare (L. Manel) and Hordeum maritimum germinated with three salt concentrations (0, 100, and 200 mM NaCl). The results showed that under unprimed conditions, salt stress significantly reduced the final germination rate, the mean daily germination, and the seedling length and dry weight. It led to a decrease in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…6). The above results are as per the findings of (33), who reported that the maximum stability in the membrane and the synthesis of the least amount of MDA along with the accumulation of osmolytes (proline content) and catalase activity in priming treatments reform the damage of morphological as well as biochemical to overcome from drought conditions (34,35). Furthermore, analysis of the correlation coefficient of studied parameters also provides a glimpse of the positive and negative relationships with priming treatments for drought tolerance (Table 2).…”
Section: Resultssupporting
confidence: 89%
“…6). The above results are as per the findings of (33), who reported that the maximum stability in the membrane and the synthesis of the least amount of MDA along with the accumulation of osmolytes (proline content) and catalase activity in priming treatments reform the damage of morphological as well as biochemical to overcome from drought conditions (34,35). Furthermore, analysis of the correlation coefficient of studied parameters also provides a glimpse of the positive and negative relationships with priming treatments for drought tolerance (Table 2).…”
Section: Resultssupporting
confidence: 89%
“…A threshold level of hydration is actually required for the synthesis of hydrolytic enzymes, which are responsible for the hydrolysis of the stored compounds in mature seeds (Rosental et al, 2014 ). Confirming previous studies (Ben Youssef et al, 2021 ; Debez et al, 2020 ; Uçarlı, 2020 ), our findings indicated that salt exposure not only impaired seed imbibition (Figure 2a ) but also led to high sodium accumulation in plant tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, calcium chloride priming was found to act on ionic balance decreasing significantly Na + accumulation in coleoptile, radicle and endosperm with respect to NPS group. Ben Youssef et al ( 2021 ) reported similar observations in barley upon use of CaCl 2 and KNO 3 seed priming, which limited the absorption and accumulation of sodium ions, maintained potassium content and decreased the sodium/potassium ratio in seedling tissues. Tian et al ( 2015 ) reported equivalent finding in wheat seedlings exposed to 100 mM NaCl after calcium application.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We found that SES1 can maintain the seedling K + /Na + balance, and the expression of K + transporter genes and ER stress-related genes were altered between WT and ses1 mutants under high potassium conditions during seedling establishment and post-germination growth. Seed priming with KCl was an effective method for alleviating seed germination caused by salt stress ( Ben Youssef et al, 2021 ) and improve emergence and seedling establishment under stress ( Ella, Dionisio-Sese & Ismail, 2011 ; Haider & Rehman, 2022 ) through a changed K + /Na + ratio. While high K + concentrations could also induce salt stress and inhibit seedling establishment and post-germination growth of plants ( Bakshi et al, 2018 ; Hassini et al, 2017 ), perhaps through plant hormone signal transduction and the mitogen-activated protein kinase signaling pathway ( Bakshi et al, 2018 ; Li et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%